The Plasmodium falciparum, Nima-related kinase Pfnek-4: a marker for asexual parasites committed to sexual differentiation - Reininger Luc (Malaria Journal, 2012)
Abstract Background Malaria parasites undergo, in the vertebrate host, a developmental switch from asexual replication to sexual differentiation leading to the formation of gametocytes, the only form able to survive in the mosquito vector. Regulation of the onset of the sexual phase remains largely unknown and represents an important gap in the understanding of the parasite’s complex biology. Methods The expression and function of the Nima-related kinase Pfnek-4 during the early sexual development of the human malaria parasite Plasmodium falciparum were investigated, using three types of transgenic Plasmodium falciparum 3D7 lines: (i) episomally expressing a Pfnek-4-GFP fusion protein under the control of its cognate pfnek-4 promoter; (ii) episomally expressing negative or positive selectable markers, yeast cytosine deaminase-uridyl phosphoribosyl transferase, or human dihydrofolate reductase, under the control of the pfnek-4 promoter; and (iii) lacking a functional pfnek-4 gene. Parasite transfectants were analysed by fluorescence microscopy and flow cytometry. In vitro growth rate and gametocyte formation were determined by Giemsa-stained blood smears. Results The Pfnek-4-GFP protein was found to be expressed in stage II to V gametocytes and, unexpectedly, in a subset of asexual-stage parasites undergoing schizogony. Culture conditions stimulating gametocyte formation resulted in significant increase of this schizont subpopulation. Moreover, sorted asexual parasites expressing the Pfnek-4-GFP protein displayed elevated gametocyte formation when returned to in vitro culture in presence of fresh red blood cells, when compared to GFP- parasites from the same initial population. Negative selection of asexual parasites expressing pfnek-4 showed a marginal reduction in growth rate, whereas positive selection caused a marked reduction in parasitaemia, but was not sufficient to completely abolish proliferation. Pfnek-4- clones are not affected in their asexual growth and produced normal numbers of stage V gametocytes. Conclusions The results indicate that Pfnek-4 is not strictly gametocyte-specific, and is expressed in a small subset of asexual parasites displaying high rate conversion to sexual development. Pfnek-4 is not required for erythrocytic schizogony and gametocytogenesis. This is the first study to report the use of a molecular marker for the sorting of sexually-committed schizont stage P. falciparum parasites, which opens the way to molecular characterization of this pre-differentiated subpopulation.